The use of emerging autonomous technologies for ocean monitoring: insights and legal challenges - Aspasia Pastra; Tafsir Matin Johansson; Joana Soares; Frank E. Muller-Karger (Frontiers in Marine Science)
The critical role of biology Essential Ocean Variables (EOVs) in advancing our understanding of marine ecosystems underscores the need for sophisticated observation tools like Autonomous Underwater Vehicles (AUVs), Unmanned Aerial Vehicles (UAVs), Maritime Autonomous Vehicles (MAVs). However, the integration of these technologies in Marine Scientific Research (MSR) has surfaced significant legal and policy challenges. This study, informed by insights from forty-six experts across academia, oceanographic institutions, industry, and intergovernmental organizations, identifies six principal legal challenges relevant to the: operation and navigation of AUVs, data collection, security, environmental impact, animal tagging, and intellectual property rights. Effectively addressing these challenges requires a coordinated, multi-stakeholder approach among the scientific community, policymakers, and international bodies. States may promote an initiative to drive progress in ocean observation while laying the groundwork for advancements. To address the operational and regulatory complexities, States may coordinate collaboration through involvement of the Intergovernmental Oceanographic Commission (IOC), the International Maritime Organization (IMO), and the World Meteorological Organization (WMO), for example. Additionally, coordination with frameworks such as the BBNJ Agreement, UNCLOS, the Convention on Biological Diversity’s Kunming-Montreal Global Biodiversity Framework (CBD KM-GBF), and regional organizations like the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) would ensure a comprehensive and inclusive approach.